Affixation of Depaha dialect - ., Ngurah Putra Bayu Krisna; ., Dr. I Gede Budasi, M.Ed.; ., Kadek Sintya Dewi, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed at 1) describing inflectional and derivational prefixes and suffixes 2) determining prefixes and suffixes which belong to inflectional morpheme and 3) determining prefixes and suffixes which belong to derivational morpheme . This research was a descriptive qualitative research. The informant sample were chosen based on set criteria and one of the important criteria was the informant must belonged to the original people of Depaha village. The data were collected based on three instruments, namely: researcher as the main instruments, tape recorder and word list. The results of the study show that there are no prefix and three suffixes in Depaha dialect. The suffixes are {-nine}, {-an}and {-nane}. All suffixes were not change the part of speech which means all suffixes belonged to derivational morpheme. There was no indication of prefixes because some words Depaha dialect were influenced by another language. Kata Kunci : Depaha dialect, Affixation, Prefixes, Suffixes, Morpheme This study aimed at 1) describing inflectional and derivational prefixes and suffixes 2) determining prefixes and suffixes which belong to inflectional morpheme and 3) determining prefixes and suffixes which belong to derivational morpheme . This research was a descriptive qualitative research. The informant sample were chosen based on set criteria and one of the important criteria was the informant must belonged to the original people of Depaha village. The data were collected based on three instruments, namely: researcher as the main instruments, tape recorder and word list. The results of the study show that there are no prefix and three suffixes in Depaha dialect. The suffixes are {-nine}, {-an}and {-nane}. All suffixes were not change the part of speech which means all suffixes belonged to derivational morpheme. There was no indication of prefixes because some words Depaha dialect were influenced by another language. keyword : Depaha dialect, Affixation, Prefixes, Suffixes, Morpheme